2010
DOI: 10.1590/s0073-47212010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of Pseudis minuta (Anura, Hylidae, Hylinae) and environmental variables related to its reproductive activity in Reserva Biológica do Lami, southern Brazil

Abstract: ABSTRACT.We studied the reproductive biology of a population of Pseudis minuta Günther, 1858 from Reserva Biológica do Lami (30º 15' S; 51º 05' W), Porto Alegre, southern Brazil. We assessed the spatial and temporal distribution of individuals (males, females, juveniles) and explored potential relationships with environmental variables. Field activities encompassed bimonthly surveys in three semi-permanent ponds, each one during approximately two days and two nights, from August 2004 to July 2005. We recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
4
1
1
Order By: Relevance
“…On the other hand, it has also been registered in calling activity throughout the year depositing the clutches in leaves above permanent water bodies (reproductive mode number 24, sensu Haddad and Prado, 2005) in moist forests. Although it is well known that the reproductive season in anuran communities is related to climatic factors (see Vaira, 2005;Zina and Haddad, 2006;Zank et al, 2010), the present study shows that domain characteristics, that are also associated with climatic factors, may not only be correlated to the duration of the reproductive season, but also act as a selective force on the reproductive mode exhibit by the species. This observation reinforces the ecological plasticity of D. minusculus.…”
Section: Discussioncontrasting
confidence: 50%
“…On the other hand, it has also been registered in calling activity throughout the year depositing the clutches in leaves above permanent water bodies (reproductive mode number 24, sensu Haddad and Prado, 2005) in moist forests. Although it is well known that the reproductive season in anuran communities is related to climatic factors (see Vaira, 2005;Zina and Haddad, 2006;Zank et al, 2010), the present study shows that domain characteristics, that are also associated with climatic factors, may not only be correlated to the duration of the reproductive season, but also act as a selective force on the reproductive mode exhibit by the species. This observation reinforces the ecological plasticity of D. minusculus.…”
Section: Discussioncontrasting
confidence: 50%
“…Previous studies of P. minuta in regions of the subtropical zone located farther inland have indicated similar positive relationships between abundance or activity patterns and temperature (Santos et al, 2008). Likewise, Zank et al (2010) found that reproductive activity in P. minuta is influenced by temperature and rainfall but not by other climatic factors. In a broader context, it has been argued that in tropical latitudes the reproductive activity of amphibians is influenced primarily by rainfall (Aichinger, 1987), whereas in temperate regions, both rainfall and temperature seem to play a major role in amphibians' reproductive behavior (Zank et al, 2010).…”
Section: Discussionmentioning
confidence: 67%
“…Likewise, Zank et al (2010) found that reproductive activity in P. minuta is influenced by temperature and rainfall but not by other climatic factors. In a broader context, it has been argued that in tropical latitudes the reproductive activity of amphibians is influenced primarily by rainfall (Aichinger, 1987), whereas in temperate regions, both rainfall and temperature seem to play a major role in amphibians' reproductive behavior (Zank et al, 2010). Hence, our findings for a subtropical region seem to agree with the results from temperate latitudes.…”
Section: Discussionmentioning
confidence: 97%
“…However, in subtropical regions -a region subjected to ecological pressure such as cold, frost, seasonality on temperature -a limited number of studies tested how ecological pressures in microhabitat scale affect the reproductive behavior of frog species (e.g. Zank et al, 2010;Huckembeck et al, 2012); for nest-building gladiator frogs, no study was found.…”
Section: Palavras-chavementioning
confidence: 99%